Math Practice Online > free > lessons > Florida > 9th grade > System of Equations Substitution

These sample problems below for System of Equations Substitution were generated by the MathScore.com engine.

## Sample Problems For System of Equations Substitution

### Complexity=3

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 - 3x + y = 6x + y = - 2 First equation solved for y: Answer (x,y): 2 x + 2y = 73x - 2y = - 3 First equation solved for y: Answer (x,y):

### Complexity=5

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 x - y = 1- 5x + y = 7 First equation solved for y: Answer (x,y): 2 4x - y = - 222x - y = - 12 First equation solved for y: Answer (x,y):

### Complexity=10

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 x + y = 55x - 8y = 25 First equation solved for y: Answer (x,y): 2 x + y = 14- 2x - y = - 18 First equation solved for y: Answer (x,y):

### Complexity=13

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 - 2x - 5y = 53-x + y = - 12 First equation solved for y: Answer (x,y): 2 - 3x - 4y = 1913x - 9y = 181 First equation solved for y: Answer (x,y):

### Complexity=14

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 x + 4y = - 5- 4x - y = 20 First equation solved for y: Answer (x,y): 2 3x + y = - 6- 7x - 5y = 30 First equation solved for y: Answer (x,y):

### Complexity=15

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
 1 - 8x + 9y = 9913x + 8y = 88 First equation solved for y: Answer (x,y): 2 - 3x - 5y = - 77- 5x + 6y = 15 First equation solved for y: Answer (x,y):

### Complexity=3

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1- 3x + y = 6
x + y = - 2
First equation solved for y:
Solution
Solve the first equation for y
- 3x + y + 3x = 6 + 3x
y = 3x + 6

Original Equations
- 3x + y = 6
x + y = - 2

Solving for y in the first equation yields:
y = 3x + 6

Substitute this into the second equation:
x + 3x + 6 = - 2
4x + 6 = - 2
Now solving for x...
4x + 6 - 6 = - 2 - 6
4x = - 8

Divide by 4

x = - 2

Now plug value of x into the original first equation
- 3(- 2) + y = 6
6 + y = 6
6 + y - 6 = 6 - 6
y = 0

2x + 2y = 7
3x - 2y = - 3
First equation solved for y:
Solution
Solve the first equation for y
x + 2y - x = 7 - x
2y = -x + 7

Divide by 2

Original Equations
x + 2y = 7
3x - 2y = - 3

Solving for y in the first equation yields:

Substitute this into the second equation:

4x - 7 = - 3
Now solving for x...
4x - 7 + 7 = - 3 + 7
4x = 4

Divide by 4

x = 1

Now plug value of x into the original first equation
1 + 2y = 7
1 + 2y = 7
1 + 2y - 1 = 7 - 1
2y = 6

Divide by 2

y = 3

### Complexity=5

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1x - y = 1
- 5x + y = 7
First equation solved for y:
Solution
Solve the first equation for y
x - y - x = 1 - x
-y = -x + 1

Multiply by - 1
 -y(- 1) = (-x + 1)(- 1)

y = x + - 1

y = x - 1

Original Equations
x - y = 1
- 5x + y = 7

Solving for y in the first equation yields:
y = x - 1

Substitute this into the second equation:
- 5x + x - 1 = 7
- 4x - 1 = 7
Now solving for x...
- 4x - 1 + 1 = 7 + 1
- 4x = 8

Divide by - 4

x = - 2

Now plug value of x into the original first equation
- 2 - y = 1
- 2 - y = 1
- 2 - y + 2 = 1 + 2
-y = 3

Multiply by - 1
 -y(- 1) = 3(- 1)

y = - 3

24x - y = - 22
2x - y = - 12
First equation solved for y:
Solution
Solve the first equation for y
4x - y - 4x = - 22 - 4x
-y = - 4x - 22

Multiply by - 1
 -y(- 1) = (- 4x - 22)(- 1)

y = 4x - - 22

y = 4x + 22

Original Equations
4x - y = - 22
2x - y = - 12

Solving for y in the first equation yields:
y = 4x + 22

Substitute this into the second equation:
2x - (4x + 22) = - 12
- 2x - 22 = - 12
Now solving for x...
- 2x - 22 + 22 = - 12 + 22
- 2x = 10

Divide by - 2

x = - 5

Now plug value of x into the original first equation
4(- 5) - y = - 22
- 20 - y = - 22
- 20 - y + 20 = - 22 + 20
-y = - 2

Multiply by - 1
 -y(- 1) = - 2(- 1)

y = 2

### Complexity=10

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1x + y = 5
5x - 8y = 25
First equation solved for y:
Solution
Solve the first equation for y
x + y - x = 5 - x
y = -x + 5

Original Equations
x + y = 5
5x - 8y = 25

Solving for y in the first equation yields:
y = -x + 5

Substitute this into the second equation:
5x - 8(-x + 5) = 25
13x - 40 = 25
Now solving for x...
13x - 40 + 40 = 25 + 40
13x = 65

Divide by 13

x = 5

Now plug value of x into the original first equation
5 + y = 5
5 + y = 5
5 + y - 5 = 5 - 5
y = 0

2x + y = 14
- 2x - y = - 18
First equation solved for y:
Solution
Solve the first equation for y
x + y - x = 14 - x
y = -x + 14

Original Equations
x + y = 14
- 2x - y = - 18

Solving for y in the first equation yields:
y = -x + 14

Substitute this into the second equation:
- 2x - (-x + 14) = - 18
-x - 14 = - 18
Now solving for x...
-x - 14 + 14 = - 18 + 14
-x = - 4

Multiply by - 1
 -x(- 1) = - 4(- 1)

x = 4

Now plug value of x into the original first equation
4 + y = 14
4 + y = 14
4 + y - 4 = 14 - 4
y = 10

### Complexity=13

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1- 2x - 5y = 53
-x + y = - 12
First equation solved for y:
Solution
Solve the first equation for y
- 2x - 5y + 2x = 53 + 2x
- 5y = 2x + 53

Divide by - 5

Original Equations
- 2x - 5y = 53
-x + y = - 12

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 5

- 7x = - 7

Divide by - 7

x = 1

Now plug value of x into the original first equation
- 2(1) - 5y = 53
- 2 - 5y = 53
- 2 - 5y + 2 = 53 + 2
- 5y = 55

Divide by - 5

y = - 11

2- 3x - 4y = 19
13x - 9y = 181
First equation solved for y:
Solution
Solve the first equation for y
- 3x - 4y + 3x = 19 + 3x
- 4y = 3x + 19

Divide by - 4

Original Equations
- 3x - 4y = 19
13x - 9y = 181

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 4

79x = 553

Divide by 79

x = 7

Now plug value of x into the original first equation
- 3(7) - 4y = 19
- 21 - 4y = 19
- 21 - 4y + 21 = 19 + 21
- 4y = 40

Divide by - 4

y = - 10

### Complexity=14

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1x + 4y = - 5
- 4x - y = 20
First equation solved for y:
Solution
Solve the first equation for y
x + 4y - x = - 5 - x
4y = -x - 5

Divide by 4

Original Equations
x + 4y = - 5
- 4x - y = 20

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 4

- 15x = 75

Divide by - 15

x = - 5

Now plug value of x into the original first equation
- 5 + 4y = - 5
- 5 + 4y = - 5
- 5 + 4y + 5 = - 5 + 5
4y = 0

Divide by 4

y = 0

23x + y = - 6
- 7x - 5y = 30
First equation solved for y:
Solution
Solve the first equation for y
3x + y - 3x = - 6 - 3x
y = - 3x - 6

Original Equations
3x + y = - 6
- 7x - 5y = 30

Solving for y in the first equation yields:
y = - 3x - 6

Substitute this into the second equation:
- 7x - 5(- 3x - 6) = 30
8x + 30 = 30
Now solving for x...
8x + 30 - 30 = 30 - 30
8x = 0

Divide by 8

x = 0

Now plug value of x into the original first equation
3(0) + y = - 6
y = - 6

### Complexity=15

Solve. When solving for y, answer in the form "y=mx+b", such as "y=3x+2" or "y=-x/3-6". Answer in the form (x,y). For example: (-2,3)
1- 8x + 9y = 99
13x + 8y = 88
First equation solved for y:
Solution
Solve the first equation for y
- 8x + 9y + 8x = 99 + 8x
9y = 8x + 99

Divide by 9

Original Equations
- 8x + 9y = 99
13x + 8y = 88

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 9

181x = 0

Divide by 181

x = 0

Now plug value of x into the original first equation
- 8(0) + 9y = 99
9y = 99
Divide by 9

y = 11

2- 3x - 5y = - 77
- 5x + 6y = 15
First equation solved for y:
Solution
Solve the first equation for y
- 3x - 5y + 3x = - 77 + 3x
- 5y = 3x - 77

Divide by - 5

Original Equations
- 3x - 5y = - 77
- 5x + 6y = 15

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 5

- 43x = - 387

Divide by - 43

x = 9

Now plug value of x into the original first equation
- 3(9) - 5y = - 77
- 27 - 5y = - 77
- 27 - 5y + 27 = - 77 + 27
- 5y = - 50

Divide by - 5

y = 10